Weaving it together - Broukal, Milada (Heinle & Heinle Publishers, 1994)
Weaving It Together, Book 3, is part of a four-level series designed to comprehensively integrate reading and writing. It promotes individualized and cooperative learning within the moderate and large-sized classroom.